Pengaruh Kepemimpinan Kepala Desa Terhadap Partisipasi Masyarakat Dalam Membayar Pajak Bumi Dan Bangunan Di Desa Koepisino Kecamatan Bonegunu - Musrifa, Musrifa; Basri, Muhammad; Abdullah, Akhyar (Universitas Halu Oleo, 2021)
The purpose of this study was to determine the effect of village head leadership on community participation in paying Land and Building Tax (PBB) in Koepisino Village, Bonegunu District. The population in this study were the taxpayers (heads of families) in Koepisino Village, as many as 177 people. The sample in this study was determined by proportional random sampling with a total sample of 64 people. The method used in this research is descriptive quantitative. Â The results in this study indicate that the leadership of the Village Head consists of dimensions 1) ways of communicating, 2) providing motivation, 3) leadership ability, 4) decision making, 5) positive power, which has a significant effect on community participation when paying Land and Building Tax (PBB). Then based on the results of the analysis of the effect of the village head on community participation in paying land and building taxes in the village of Koepisino, Bonegunu District, it shows that the effect of the village head is 58.3% and the remaining 41.7% is caused by other factors. Then the leadership dimension of the Village Head in Koepisino Village that gives the highest contribution to community participation in paying land and building taxes is the dimension of how to communicate. Meanwhile, the leadership dimension of the Village Head in Koepisino Village which gives the lowest contribution to community participation in paying land and building taxes is a positive dimension of power.